Persepsi Mahasiswa Surakarta Terhadap Dialek Jawa Surabaya(Deskriptif Kualitatif Komunikasi Pada Mahasiswa Surakarta Jurusan Ilmu Komunikasi Fakultas Komunikasi dan Informatika Universitas Muhammadiyah Surakarta) - Atmojo, Wahyu Tri, Ratri Kusumaningtyas, M. Si (2017)
There are various aspects in Indonesia, therefore the people of Indonesia are often referred to as the characteristics of a plural Indonesian society. Bhinneka Tunggal Ika is the motto of Indonesia which means although different but still one united nation. The motto is used as a symbol of this country that has a variety of diversities. Communication contains elements of language which is used as a tool for communication process. The use of language as a means of communication is strongly influenced vy the culture of each individual. In the study of language there is a term called dialect. Dialects are variations of language. Cultural communication is the communication used for the transformation of messages by communication actors with different cultural backgrounds. The dialect of each region has differences with other regions. This dialect has differences because it is adjusted by the may not be accepted by the other groups. There is a rejection of the coming of another culture by a particular group due to the involvement of the ego of an individual group. This distinction forms the perception of the dialect's appraisal of other cultures. This perception can lead to misunderstandings that end in conflict between social groups. This study aimed to explain the style of Surakarta dialect and Surabaya dialect. Besides, it also aimed to know the efforts of Surakarta students to face Surabaya students who have different forms of dialect. The results of this study indicated that the Surabaya dialect is consideres less effective. Surakarta students perceived that the Surabaya dialect is less suitable to be used to communicate in the Surakarta student ego. Surakarta students had a perception that the dialect of Surabaya has no faults but only poorly used to communicate in the Surakarta region.